Control of natural convection in a CNT-water nanofluid filled 3D cavity by using an inner T-shaped obstacle and thermoelectric cooler - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2020)
Natural convection of CNT-water nanofluid in a 3D cavity with an inner T-shaped adiabatic obstacle is studied. The cold surface temperature of the enclosure is controlled by using a thermoelectric cooler while the hot surface of the cavity is made inclined. Numerical simulations are performed by using Galerkin weighted residual finite element method. Impact of various pertinent parameters such as current flux of the thermoelectric cooler (between 0.01 A/mm(2) and 0.04 A/mm(2)), ambient temperature (between 298 K and 313 K), inclination of the side surface of 3D cavity (between 0 and 40 center dot), inclination of the T-shaped obstacle (between -90 degrees and 90 degrees), size of the obstacle (between 0.1 H and 0.4 H) and solid nanoparticle volume fraction (between 0 and 4%) on the natural convective heat transfer features is numerically examined. It was observed the local and average heat transfer rates are enhanced with higher values of current flux of the thermoelectric element and solid nanoparticle volume fraction while the effect is reverse with higher hot side temperature of the thermoelectric element and cavity side surface inclination angle. As compared to others, size and inclination of the T-shaped obstacle have slight effects on the variation of Nusselt number and maximum deviation of 6% in the average heat transfer is obtained when the orientation of the obstacle is changed from -45 degrees to -90 degrees. When the minimum and maximum values of cavity inclination angles are compared, 23.70% of reduction in the average Nusselt number is obtained. The heat transfer augmentation with CNT-nanoparticle inclusion is significant and 128% enhancement in the average Nusselt number is achieved at the highest solid nanoparticle volume fraction.
Keywords: CNT-nanofluid; Thermoelectric cooler; Finite element method; 3D Cavity; T-shaped object